Exchange Rates, Policy Convergence, and the European Monetary System - MacDonald, Ronald; Taylor, Mark P. (The Review of Economics and Statistics, 1991)
We analyze the degree of policy convergence of EMS member countries relative to that of some non-EMS countries. Interestingly, we find convergence for the nominal and real exchange rates and money supplies of the EMS members but not for the non-EMS countries. We also provide some evidence to support the "German leadership hypothesis" in the context of intra-EMS monetary policy convergence.